2003
DOI: 10.1097/00006205-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

New Guidelines for Heart Failure Focus on Prevention

Abstract: Heart failure is the only major cardiovascular disease that's increasing in incidence and prevalence in the United States. Because heart failure is a preventable disease, the 2002 heart failure guidelines devise a new staging system that expands the continuum of care to encompass prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The pathophysiological mechanism of CHD leading to HF via cardiac dysfunction is also well-established. Our own studies and others have also shown that renal failure, COPD, and diabetes mellitus may lead to cardiac dysfunction through microvascular damages and inflammation [24][25][26][27]. The elevated co-morbidity rate of pneumonia in the older adult patients with HF may be due mainly to the functional weakening of their immune system [28][29][30][31][32].…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological mechanism of CHD leading to HF via cardiac dysfunction is also well-established. Our own studies and others have also shown that renal failure, COPD, and diabetes mellitus may lead to cardiac dysfunction through microvascular damages and inflammation [24][25][26][27]. The elevated co-morbidity rate of pneumonia in the older adult patients with HF may be due mainly to the functional weakening of their immune system [28][29][30][31][32].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Given the available knowledge from literatures, these diseases share the most similar risk factors with each other, such as obesity and hypertension. CHD, CBVD, COPD, diabetes mellitus, and renal failure have often been suggested as risk factors for HF [25][26][27]40]. Of the six selected comorbidities, CHD was the most common co-morbidity in HF patients.…”
Section: Principal Findingsmentioning
confidence: 99%